Anti-inflammatory Principles of the Plant Family Amaryllidaceae - Nair, Jerald J.; van Staden, Johannes (Planta Medica, 2024)
There is considerable interest in the utilisation of plants against inflammation. Over 50 species of the plant family Amaryllidaceae are known for such usage in traditional medicine. This review was undertaken to identify the chemical principles responsible for these anti-inflammatory effects. It describes the findings from in vitro, in vivo and in silico studies, as well as the probes made on the mechanisms of action. The literature search returned over 600 hits, of which around 130 were chosen for their relevance to the text. Over 140 compounds have thus far been screened for anti-inflammatory effects. These were mostly isoquinoline alkaloids but also included other classes of secondary metabolites such as chromones, flavonoids and triterpenoids. In vitro studies were carried out in mononuclear cells such as lymphocytes, monocytes, neutrophils and macrophages, against which no serious side effects were observed. The constituents were also effective against inflammation induced by physical and chemical stimuli in a variety of murine test subjects. Chief among the compounds were the isoquinoline alkaloids lycorine and narciclasine, which displayed potent effects against pain, swelling, asthma and arthritis, amongst others. From a mechanistic perspective, several of the compounds were shown to mediate in inflammatory pathways, notably via the modulation of both pro-inflammatory (such as NF-κB, TNF-α and IL-1) and anti-inflammatory (such as IL-10 and TGF-β) factors. Useful insights also emerged from active-site docking studies of some of the compounds. The Amaryllidaceae affords a rich and diverse platform for the discovery of potential anti-inflammatory drugs.
Keywords: alkaloid; Amaryllidaceae; anti-inflammatory; drug discovery; medicinal plant